2016
DOI: 10.2147/copd.s104051
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care procalcitonin test to reduce antibiotic exposure in patients hospitalized with acute exacerbation of COPD

Abstract: BackgroundThis study was conducted to investigate whether point-of-care (POC) procalcitonin (PCT) measurement can reduce redundant antibiotic treatment in patients hospitalized with acute exacerbation of COPD (AECOPD).MethodsOne-hundred and twenty adult patients admitted with AECOPD were enrolled in this open-label randomized trial. Patients were allocated to either the POC PCT-guided intervention arm (n=62) or the control arm, in which antibiotic therapy followed local guidelines (n=58).ResultsThe median dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 28 publications
0
63
2
4
Order By: Relevance
“…The impact of PCT monitoring in patients with LRTIs was studied in a variety of randomized controlled trials, mainly in the inpatient setting (Table ). Overall, studies in this patient population demonstrated that PCT monitoring, when compared with standard care (no PCT monitoring), results in a reduction in antibiotic therapy duration in the range of 0–8 days, with no corresponding impact on infection relapses . A large meta‐analysis detected a significant reduction in 30‐day mortality in patients with acute respiratory infections receiving PCT‐guided therapy compared with those receiving standard care (9% vs 10%; adjusted OR 0.83, 95% CI 0.70–0.99, p=0.37, respectively) .…”
Section: Procalcitonin As a Determinant Of Antibiotic Therapy Durationmentioning
confidence: 87%
See 1 more Smart Citation
“…The impact of PCT monitoring in patients with LRTIs was studied in a variety of randomized controlled trials, mainly in the inpatient setting (Table ). Overall, studies in this patient population demonstrated that PCT monitoring, when compared with standard care (no PCT monitoring), results in a reduction in antibiotic therapy duration in the range of 0–8 days, with no corresponding impact on infection relapses . A large meta‐analysis detected a significant reduction in 30‐day mortality in patients with acute respiratory infections receiving PCT‐guided therapy compared with those receiving standard care (9% vs 10%; adjusted OR 0.83, 95% CI 0.70–0.99, p=0.37, respectively) .…”
Section: Procalcitonin As a Determinant Of Antibiotic Therapy Durationmentioning
confidence: 87%
“…The authors cited modest adherence and lack of serial PCT measurements as potential factors contributing to the lack of observed benefits. In other studies, adherence to PCT algorithms varies greatly, ranging from 47–97% …”
Section: Challenges Implementing Pct Monitoringmentioning
confidence: 98%
“…Inflammatory markers as a kind of quantitative indicator are widely used in judging acute exacerbation and assessing prognosis. Systemic inflammatory markers mainly include CRP,1719 PCT,20,21 serum amyloid A,22 SP-D,23 fibrinogen,24 inflammation cell chemotactic factor,25 and so on. All the markers mentioned earlier will increase in AECOPD patients and decrease in recovery.…”
Section: Methodsmentioning
confidence: 99%
“…However, in patients with more severe disease and/or exacerbations, Gram-negative pathogens, such as Pseudomonas aeruginosa , are common,79,80 and may prove more challenging to treat in light of increasing resistance in some regions. The role of procalcitonin as a potential biomarker for optimizing antibiotic-treatment strategy in COPD exacerbations (especially those induced by bacterial infection) is also being investigated; however, as yet its role is unproven 81,82. Further studies are required to guide optimal antibiotic treatment, based on investigation of biomarkers to identify patients expected to benefit, and to establish the optimal duration of treatment 83…”
Section: What Are the Recommended Treatment Strategies For Severe Copmentioning
confidence: 99%